A coefficient clustering analysis for damage assessment of composites based on pulsed thermographic inspection. (October 2016) - Zhao, Yifan; Tinsley, Lawrence; Addepalli, Sri; Mehnen, Jörn; Roy, Rajkumar
Abstract: This paper introduces a coefficient clustering analysis method to detect and quantitatively measure damage occurring in composite materials using pulsed thermographic inspection. This method is based on fitting a low order polynomial model for temperature decay curves, which (a) provides an enhanced visual confirmation and size measurement of the damage, (b) provides the reference point for sound material for further damage depth measurement, (c) and reduces the burden in computational time. The performance of the proposed method is evaluated through a practical case study with carbon fibre reinforced polymer (CFRP) laminates which were subjected to a drop impact test with varying energy levels. A novel method for reducing an entire thermogram sequence into a single image is introduced, which provides an enhanced visualisation of the damage area. Highlights: A coefficient clustering analysis method to assess damage in composite materials is proposed. Distribution of estimated coefficients provides an alternative to characterise damage. This technique not only provides an enhanced visual confirmation of the damage, but also reduces the burden on the operator in post-processing the data. Improvement to suitability of pulsed thermography to assess impact damage in composites.